Elastic analysis of axially functionally graded rotating thick cylinder with variable thickness under non-uniform arbitrarily pressure loading. (April 2015) - Nejad, Mohammad Zamani; Jabbari, Mehdi; Ghannad, Mehdi
Abstract: A functionally graded rotating thick hollow cylinder with variable thickness and clamped ends is studied semi-analytically under arbitrarily non-uniform pressure on the inner surface. The material properties, except the Poisson's ratio, are assumed to vary with the power law function in the axial direction of the cylinder. By using the first-order shear deformation theory (FSDT) the governing equations are derived. The governing equations are in the form of a set of general differential equations. Given that the FG cylinder with variable thickness is divided into n homogenous disks, n sets of differential equations are obtained. The solution of this set of equations is obtained, applying the boundary conditions and continuity conditions between the layers, radial displacement and stresses. The problem is also solved, using the finite element method (FEM). The obtained results of the disk form multi-layers method (MLM) are compared with those of FEM.